Odpowiedzi

2010-03-13T14:45:46+01:00
A. 12-2(x-1)^2 = 4(x-2)-(x-3)(2x-5)
12-2(x^2-2x+1)=4x-8-2x^2+5x+6x-15
12-2x^2x-2=15x-23-2x^2
10-2x^2=15x-23-2x^2
-15x=-33/:(-15)
x=2,2
B.(x+3)^2-(x-5)^2 = 16(x-1)
x^2+6x+9-x^2+10x-25=16x-16
16x-16=16x-16
0=0
C.(x+5)(y-2)=(x+2)(y-1)
xy-2x+5y-10=xy-x+2y-2
-x+3y=8/:(-1)
x=3y-8
-(3y-8)+3y=8
-3y+8+3y=8
0=0
D.(x-4)(y+7)=(x-3)(y+4)
xy+7x-4y-28=xy+4x-3y-12
3x-y=16/:(-1)
y=3x-16
3x-(3x-16)=16
3x-3x+16=16
0=0
1 1 1
2010-03-13T14:51:07+01:00
A. 12-2x^2+4x-2=4x-8-2x^2+5x+6x-15
33=11x
x=3

B. x^2+6x+9-x^2+10x-25=16x-16
0=0
Tożsamościowe

C.
xy-2x+5y-10=xy-x+2y-2
-x+3y=8

D.
xy+7x-4y-28=xy+4x-3y-12
3x-y=16
1 1 1
2010-03-13T14:54:45+01:00
A i B w załącznikach ;)


C.(x+5)(y-2)=(x+2)(y-1)
xy-2x+5y-10=xy-x+2y-2
-2x+x+5y-2y=-2+10
-x+3y=8



D.(x-4)(y+7)=(x-3)(y+4)
xy+7x-4y-28=xy+4x-3y-12
3x-y=16


1 1 1